Comparison in attacking & defending patterns between Spain & England football teams in Euro 2024 - Abdullah, Ahmad Danial Azman; Mohamed, Muhamad Noor; Adnan, Muhamad Aizzat; Saiful Annur, Muhamad Safiq (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study analyzes the tactical patterns of Spain and England during UEFA Euro 2024, examining both attacking and defending strategies through the lens of complex sociotechnical systems. By integrating tournament-specific data from 11 matches, including the final, the research bridges a gap in national team analysis that typically isolates individual phases of play. The findings provide a comprehensive overview of how direct counterattacks and possession-based styles interact within a dynamic, high-stakes tournament environment.